2010
DOI: 10.1038/jid.2009.227
|View full text |Cite
|
Sign up to set email alerts
|

Vaccines and Microbicides Preventing HIV-1, HSV-2, and HPV Mucosal Transmission

Abstract: HIV-1, herpes simplex virus type 2 (HSV-2), and human papillomavirus (HPV), among other sexually transmitted infections, represent a major burden for global health. Initial insights into the mucosal transmission of these viral pathogens have raised optimism with regard to the rapid generation of protective vaccines. Nevertheless, setbacks for HIV-1 and HSV-2 vaccines have seriously challenged the initial enthusiasm. Recently, two new vaccines that efficiently prevented HPV infection have renewed the hope that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 126 publications
0
18
0
Order By: Relevance
“…Even more disappointingly, vLAW-gB1/RD afforded no protection against HSV-1 challenge. In contrast, the vLAW-gB1/VSV vaccinees were fully protected from disease, paralleling the results obtained from most HSV vaccines hitherto developed (17,38).…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations
“…Even more disappointingly, vLAW-gB1/RD afforded no protection against HSV-1 challenge. In contrast, the vLAW-gB1/VSV vaccinees were fully protected from disease, paralleling the results obtained from most HSV vaccines hitherto developed (17,38).…”
Section: Discussionmentioning
confidence: 48%
“…In general, these vaccines, whether tested in animal models or clinical studies, prevented HSV-1 disease but were poorly protective against lethal doses of HSV-1 and were clearly inadequate against HSV-2. The studies also showed that mucosal immunity is important to prevent or curb the course of infection (17,27,30,38).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternative strategies have emerged, with the use of microbicides, aimed at targeting and preventing specific steps of viral transmission upon mucosal surfaces challenge by HIV-1 (reviewed in [43]). …”
Section: Potential Strategies To Block Hiv Transmissionmentioning
confidence: 99%